Synthesis and characterization studies of polypyrrole/iron tungstate nanocomposites for interfacial water evaporation. Issue 1 (1st January 2022) - Robert Bellarmin, V; Moorthy, Arjun; Raja Saravanan, M. E.
Abstract: PPy-FeWO4 composites were synthesized by polymerization of pyrrole in presence of varying weight percentage of FeWO4 nanoparticles using FeCl3 as both catalyst and dopant. The synthesized polymer composites were characterized by FTIR, XRD, FESEM-EDAX, TEM and TGA analysis. The XRD and FTIR analysis confirmed showing near pure samples were achieved. The FESEM-EDAX and TEM studies showed the presence of FeWO4 nanoparticles which were well dispersed in the polymer matrix. The thermal degradation studies showed similar stability of polymer matrix in the presence of nanoparticles. Interfacial solar water evaporation devices were fabricated by depositing the polymer composite on floatable PU sponges. The studies revealed that 50-50 wt% PPy-FeWO4 showed maximum solar to vapour conversion up to 86% with an evaporation rate up to 1.2 kg m −2 hr −1 .